More Material Combinations, Lower Costs - Moritzer, Elmar; Mühlhoff, Frederik Marvin; Krampe, Erhard; Böhnke, Birte (Kunststoffe international)

Neuartige Fügetechnik für Organoblech-Hybridverbindungen - Moritzer, Elmar; Krassmann, Dimitri (DVS Congress 2020)

Neue Maßstäbe in puncto Festigkeit und Faserlänge - Moritzer, Elmar; Wittke, M. (Plastverarbeiter)

Plasma technology rationalizes 2-component processes - Moritzer, Elmar; Mühlhoff, Frederik Marvin; Krampe, Erhard; Böhnke, Birte (adhesion ADHESIVES + SEALANTS)

Plasma-Technologie zur Rationalisierung von 2K-Prozessen - Moritzer, Elmar; Mühlhoff, Frederik Marvin; Krampe, Erhard; Böhnke, Birte (adhäsion KLEBEN & DICHTEN)

Spritznieten als neue Organoblech-Metall-Hybridfügetechnik

Stainless steel parts produced by Fused Deposition Modeling and a sintering process compared to components manufactured in Selective Laser Melting - Moritzer, Elmar; Schumacher, C. (4th International Conference Progress on Polymers and Composites Products and Manufacturing Technologies (POLCOM))

Wechseldehnungsschweißen - Entwicklung einer Fügetechnologie für 3D-Geometrien - Vogtschmidt, Sascha; Fiebig, Isabel; Schöppner, Volker (Joining Plastics)

Differences between the recycled carbon fibers especially regarding the product quality, - Malatyali, Hatice; Schöppner, Volker; Behrendt, Alexander; Hoemann, Theresa; Sporkmann, Frederick; Hanselle, Felix (SPE ANTEC)

Wechseldehnungsschweißen - Entwicklung einer Fügetechnologie für 3D-Geometrien - Vogtschmidt, Sascha; Schöppner, Volker (DVS CONGRESS 2020 - Große Schweißtechnische Tagung)

Vibration welding of components with angled areas in the direction of vibration - Vogtschmidt, Sascha; Schöppner, Volker (Welding in the World)

Schweißnahtkennwerte für die lebensdaueroptimierte Bauteilauslegung von hochtemperaturbeständigen Thermoplasten - Vogtschmidt, Sascha; Schöppner, Volker (Joining Plastics)

Antecedents and Performance Consequences of High-Potential Scheme Use - Krebs, Benjamin (Academy of Management Proceedings)

Kunststofftechnik Paderborn: Entwicklung von Scale-Up-Regeln für das quasisimultane Laserdurchstrahlschweißen von Thermoplasten - Arndt, Theresa; Schöppner, Volker (Joining Plastics)

Wenn Regeln Potenziale freisetzen - Arndt, Theresa; Schöppner, Volker (K-Zeitung)

Quasi-Simultaneous Laser Transmission Welding - Arndt, Theresa; Schöppner, Volker (PhotonicsViews)

Modellierung des Wärmetransports in zyklisch durchströmten Wärmeübertragern - Mügge, Nils; Kronberg, Alexander; Glushenkov, Maxim; Kenig, Eugeny (Jahrestreffen der ProcessNet-Fachgruppe „Energieverfahrenstechnik“)

Influence of Material Degradation on Weld Seam Quality in Hot Gas Welding of Polyamides - Schöppner, Volker; Bialaschik, Max (73th Annual Assembly of the International Institute of Welding (IIW))

From filament production to material qualification for the FDM process - Moritzer, Elmar; Wächter, Julian

Interdiffusion in aluminum-steel clad strip - Krivská, Barbora; Šlapáková, Michaela; Kihoulou, Martin; Králík, Rostislav; Bajtošová, Lucia; Cieslar, Miroslav; Grydin, Olexandr; Stolbchenko, Mykhailo; Schaper, Mirko (Proc. 20th Conference of Czech and Slovak Physicists)

Device for twin-roll casting of strips with profiled cross-section - Bondarenko, Serhii; Grydin, Olexandr; Oginskiy, Yosyp; Kuzmina, Olga; Frolov, Yaroslav (Theory and practice of metallurgy)
Goal. This article is devoted to the development of a new method of roll-crystallizers profiling for twin-roll casting in order to provide the possibility of manufacturing strips with variable geometry on width as one of the more widely used products in the world. Method. The proposed method of profiling is implemented by using profiling strips that cover one or both rolls-crystallizers. In this way achieved profiling of the surface of the cylindrical internally water-cooled rolls, which corresponds to the desired type of strips profiled cross-section. Research results. For the practical implementation of the proposed profiling method was developed device for twin-roll of strips with profiled cross- section. In this paper presented the basic scheme of developed device for twin-roll casting of strips with profiled cross-section using endless strips and given the principle of operation of developed device for profiling. Scientific novelty. A feature of the developed device is its universality, which provides the possibility of synchronous rotation of tension, profiled and compensating-tension rollers in perpendicular plane to the axis of rotation of the rolls-crystallizers. This implementation of the device for twin-roll casting allows to manufacture different types of strips with profiled cross-section. Practical significance. For developed device for twin-roll casting of strips with profiled cross-section has been obtained patent for the invention of Ukraine. For further practical implementation of the developed device, considering the adjustments that provide practical implementation on a specific laboratory twin-roll casting unit, the device of twin-roll casting of strips with profiled cross-section was designed. In the work are presented the basic structural elements and their appearance in the form of three-dimensional models.

Aluminum-steel clad material prepared by twin-roll casting - KŘIVSKÁ, Barbora; ŠLAPÁKOVÁ, Michaela; Grydin, Olexandr; CIESLAR, Miroslav (METAL 2020 Conference Proeedings)

Deformation of expanded steel mesh inlay inside aluminum matrix during the roll bonding - Frolov, Yaroslav; Haranich, Yurii; Bobukh, Olexandr; Remez, Oleg; Voswinkel, Dietrich; Grydin, Olexandr (Journal of Manufacturing Processes)

Cold rolling of pre-profiled strips from aluminum alloy EN AW-1050 - Bondarenko, Serhii; Grydin, Olexandr; Frolov, Yaroslav; Kuzmina, Olga; Bobukh, Olexandr (Modern Problems of Metallurgy – Scientific Bulletin)

Large-scale heat pumps: Uptake and performance modelling of market-available devices - Jesper, Mateo; Schlosser, Florian; Pag, Felix; Walmsley, Timothy Gordon; Schmitt, Bastian; Vajen, Klaus (Renewable and Sustainable Energy Reviews)

Integration von Wärmepumpen zur Dekarbonisierung der industriellen Wärmeversorgung - Schlosser, Florian

Heat Pump Bridge Analysis Using the Modified Energy Transfer Diagram - Schlosser, Florian; Wiebe, Heinrich; Walmsley, Timothy G.; Atkins, Martin J.; Walmsley, Michael R. W.; Hesselbach, Jens (Energies)
Heat pumps are the key technology to decarbonise thermal processes by upgrading industrial surplus heat using renewable electricity. Existing insight-based integration methods refer to the idealised Grand Composite Curve requiring the full exploitation of heat recovery potential but leave the question of how to deal with technical or economic limitations unanswered. In this work, a novel Heat Pump Bridge Analysis (HPBA) is introduced for practically targeting technical and economic heat pump potential by applying Coefficient of Performance curves into the Modified Energy Transfer Diagram (METD). Removing cross-Pinch violations and operating heat exchangers at minimum approach temperatures by combined application of Bridge Analysis increases the heat recovery rate and reduce the temperature lift to be pumped at the same time. The insight-based METD allows the individual matching of heat surpluses and deficits of individual streams with the capabilities and performance of different market-available heat pump concepts. For an illustrative example, the presented modifications based on HPBA increase the economically viable share of the technical heat pump potential from 61% to 79%.

Large-scale heat pumps: Applications, performance, economic feasibility and industrial integration - Schlosser, F.; Jesper, M.; Vogelsang, J.; Walmsley, T.G.; Arpagaus, C.; Hesselbach, J. (Renewable and Sustainable Energy Reviews)

Kombination und Integration etablierter Technologien mit additiven Fertigungsverfahren - Lieneke, Tobias; Künneke, Thomas; Eschner, Niclas; Jacob, Alexander; Schäfer, Martin; Hickmann, Thorsten; Faroun, Rami; Hoffmann, Markus; Scholl, Markus; Baumeister, Kai; Zimmer, Detmar; Lanza, Gisela

Efficient Cryptographic Constructions with Strong Security Guarantees - Kurek, Rafael

Transfer und Kooperation im regionalen Kontext. Erfahrungen aus der Forschung zu kommunalem Bildungsmanagement - Peter F. E. Sloane, Dieter Euler, Tobias Jenert (Berufsbildung in Wissenschaft und Praxis)

Neuartige Fügetechnik für Organoblech-Hybridverbindungen

Spritznieten als neue Organoblech-Metall-Hybridfügetechnik

Pre-seasonal Assessment and Performance Diagnostics: Orthopaedic and Functional Aspects - Gokeler, Alli; Büchel, Daniel (Injury and Health Risk Management in Sports)

Peer Mentoring an der Fakultät für Wirtschaftswissenschaften - Konzept und Realisierungsformen - Sloane, Hannah; Kremer, H.-Hugo (Mentoring in Hochschuldidaktik und -praxis - Eine Reflexion wissenschaftlicher Erkenntnisse und praktischer Erfahrungen)

Interferometric method for determining the losses of spatially multi-mode nonlinear waveguides based on second harmonic generation - Santandrea, Matteo; Stefszky, Michael; Roeland, Ganaël; Silberhorn, Christine (Optics Express)

Experimental control of the degree of non-classicality via quantum coherence - Smirne, A; Nitsche, T; Egloff, D; Barkhofen, Sonja; De, S; Dhand, I; Silberhorn, Christine; Huelga, S F; Plenio, M B (Quantum Science and Technology)

Long‐term effects of hydrolyzed formulae on atopic diseases in the GINI study - Gappa, Monika; Filipiak‐Pittroff, Birgit; Libuda, Lars; Berg, Andrea; Koletzko, Sibylle; Bauer, Carl‐Peter; Heinrich, Joachim; Schikowski, Tamara; Berdel, Dietrich; Standl, Marie (Allergy)

A mendelian randomization study on causal effects of 25(OH)vitamin D levels on attention deficit/hyperactivity disorder - Libuda, Lars; Naaresh, Roaa; Ludwig, Christine; Laabs, Björn-Hergen; Antel, Jochen; Föcker, Manuel; Hebebrand, Johannes; Hinney, Anke; Peters, Triinu (European Journal of Nutrition)
Abstract Background While observational studies revealed an inverse association between serum 25(OH)vitamin D (25(OH)D) and the risk of attention deficit/hyperactivity disorder (ADHD), the causality of this relationship remains unclear. Methods We conducted a bidirectional two-sample Mendelian Randomization (MR) study to examine whether 25(OH)D has an effect on the risk to develop ADHD or vice versa. Information on single nucleotide polymorphisms (SNP) associated with serum 25(OH)D was obtained from a genome-wide association study (GWAS) considering phenotype data from 79,366 individuals of European ancestry. Data on risk for ADHD were derived from a GWAS analysis with 20,183 individuals diagnosed with ADHD and 35,191 controls. For our analysis, we considered effect sizes based on the European participants (19,099 cases and 34,194 controls). Results Single SNP analyses showed a causal effect of vitamin D on ADHD risk for only one SNP (rs12785878, p = 0.024). The overall MR estimates did not reveal a causal effect of 25(OH)D on risk for ADHD. In the reverse analysis, neither any single nor the multi-SNP MR analyses showed a causal effect of ADHD on 25(OH)D. Conclusion Results from this two-sample MR study did not confirm a causal effect of 25(OH)D on ADHD or vice versa. Accordingly, our study does not provide evidence that improving 25(OH)D via supplementation could reduce the risk of developing ADHD.

The overall diet quality in childhood is prospectively associated with the timing of puberty - Duan, Ruonan; Qiao, Tian; Chen, Yue; Chen, Mengxue; Xue, Hongmei; Zhou, Xue; Yang, Mingzhe; Liu, Yan; Zhao, Li; Libuda, Lars; Cheng, Guo (European Journal of Nutrition)
Abstract Purpose The influences of nutrition in childhood on puberty onset could have sustained consequences for health and wellbeing later in life. The aim of this study was to investigate the prospective association of diet quality prior to puberty with the timing of puberty onset. Methods We considered data from 3983 SCCNG (Southwest China Childhood Nutrition and Growth) study participants with dietary data, anthropometric measurement, and information on potential confounders at their baseline assessment (mean age: 7.1 years for girls and 7.3 years for boys; mean length of follow-up was 4.2 years). Cox proportional hazard regression estimating hazard ratios (HRs) and 95% confidence intervals (CIs) were used to examine the relationship between diet quality and puberty onset. Dietary intake at baseline was assessed using a validated food frequency questionnaire. Diet quality was determined using the Chinese Children Dietary Index (CCDI) which measures adherence to current dietary recommendations (theoretical range: 0–160 points). Age at Tanner stage 2 for breast/genital development (B2/G2), menarche or voice break (M/VB) were used as pubertal markers. Results The CCDI score ranged from 56.2 to 136.3 for girls and 46.1–131.5 for boys. Pubertal markers consistently indicate that girls and boys with higher diet quality were more likely to enter their puberty later than their counterparts with lower CCDI scores (higher vs. lower CCDI tertiles: adjusted HR for age at B2: 0.85 (95% CI, 0.81–0.94), p for trend = 0.02; G2: 0.86 (95% CI,0.80–0.96), p for trend = 0.02; M: 0.86 (95% CI,0.80–0.95), p for trend = 0.02; VB: 0.86 (95% CI,0.79–0.98), p for trend = 0.03), after adjustment for paternal education level, baseline energy intake, and pre-pubertal body fat. Conclusions Our data suggested a later puberty onset and later timing of progressed puberty stages in children with a high diet quality, which were independent of pre-pubertal body fat.

Qualifizierung von Studierenden des Grund- und Förderschullehramts für den inklusiven Unterricht in der Grundschule - Franzen, Katja; Görel, Gamze; Hellmich, Frank; Filipiak, Agnes; Albers, Timm (Sonderpädagogik und Bildungsforschung – Fremde Schwestern?)

School-based interventions to support student participation. A comparison of different programs. Results from the FRIEND-SHIP project - Hassani, Sepideh; Aroni, Katerina; Schwab, Susanne; Resch, Katharina; Toulia, Anastasia; Alves, Silvia; Görel, Gamze; Löper, Marwin Felix; Avramidis, Elias; Silveira- Maia, Mónica; Sanches-Ferreira, Manuela; Hellmich, Frank

Unterschiede in den Einstellungen zur Teamarbeit im inklusiven Unterricht zwischen Studierenden des Grund- und Förderschullehramts - Hoya, Fabian Karl; Schulze, Jan Roland; Hellmich, Frank (Sonderpädagogik und Bildungsforschung – Fremde Schwestern?)

Expertiseentwicklung: Umwandlung von Wissen in Können - Harteis, Christian; Billett, Stephen; Gruber, Hans (Implizites Wissen. Berufs- und wirtschaftspädagogische Annäherungen)

Einstellungen von Kindern gegenüber Peers mit Förderbedarf: Die Rolle persönlicher Ressourcen für die soziale Partizipation. - Löper, Marwin Felix

Determinanten für die Einstellungen von Grundschulkindern gegenüber Peers mit einem sonderpädagogischen Förderbedarf in der emotionalen und sozialen Entwicklung - Löper, Marwin Felix; Hellmich, Frank (Sonderpädagogik und Bildungsforschung – Fremde Schwestern?)

Die Ernährungsversorgung in Familien zwischen Zeit, Alltag und Haushaltsführung. Eine Mixed-Methods-Untersuchung - Klünder, Nina

Der Jugendamts-Monitor. Aufgaben – Trends – Daten - Müller, Heinz; Klünder, Nina

Optimal and Greedy Heuristic Approaches for Scheduling and Mapping of Hardware Tasks to Reconfigurable Computing Devices - Guetttatfi, Zakarya; Kaufmann, Paul; Platzner, Marco (Proceedings of the International Workshop on Applied Reconfigurable Computing (ARC))

Intrinsic Quality Assessment of Arguments - Wachsmuth, Henning; Werner, Till (Proceedings of COLING 2020, the 28th International Conference on Computational Linguistics)